Conventional versus adjustable pulmonary artery banding: which is preferable?. (6th March 2014) - Talwar, Sachin; Kumar, Manikala Vinod; Choudhary, Shiv Kumar; Airan, Balram
Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was 'whether conventional pulmonary artery banding (PAB) or adjustable PAB might be the superior intervention?' Using the PubMed search, 51 papers were found, of which seven papers represented the best evidence to answer the clinical question. We included only those papers that actually compared conventional PAB with adjustable PAB, and excluded those that studied only one of these interventions. Four studies qualified (one prospective and three retrospective) and analysed data in human patients, while three were experimental studies in animals. The end points in the prospective human study were death, debanding and follow-up to intracardiac repair. The three retrospective studies compared the incidence of early deaths, inotropic support, need for mechanical ventilatory support, reoperations and intensive care unit and hospital stay. Out of the four studies in humans, three studies noted a significant reduction in early deaths from 23 to 1.8%, 77 to 0% and 15 to 0% in conventional vs adjustable PAB. Need for early reoperations reduced from 18 to 3.5% and from 35 to 0% in 2 studies. Similarly, there was a reduction in the ventilatory times and the intensive care unit and hospital stay. The three experimental animal studies demonstrated that a much more reliable preparation of the ventricle was achieved with the use of an adjustable PAB. The results of all the seven studies led us to conclude that adjustable PAB provides superior early outcomes; reduces early mortality, need for inotropes and need for reintervention; and provides equivalent or superior band gradients when compared to conventional PAB. The use of the adjustable PAB was found to result in significant haemodynamic improvement by progressively reducing the pulmonary artery pressures and left-to-right shunt. The adjustable PAB was found to improve early survival and also made delayed repair feasible in a better clinical state, with reduced mortality and morbidity.